Design scheme of physical layer security for intelligent reflecting surface-assisted MISO communication system - Xiaorong JING; Zhenyuan SONG; Wei GAO; Weijia LEI; Qianbin CHEN (Tongxin xuebao)
Intelligent reflecting surface (IRS) improves the physical layer security of the communication systems by adjusting the phases of the reflecting units.A scheme of physical layer security design based on alternative iteration was proposed for IRS-assisted multiple input single output (MISO) communication system.Firstly, aiming at maximizing the secrecy rate, a non-convex objective function with non-convex constraints was constructed.Secondly, the Dinkelbach algorithm and Riemannian manifold optimization algorithm were adopted to transform the non-convex problem into a series of solvable sub-problems.Finally, the alternate iteration method was used to achieve the optimization design of transmit beamforming and IRS phase shift matrix.The simulation results show that, compared with the several existing schemes, the proposed scheme can achieve a better tradeoff between computational complexity and system security rate.